Al(NO3)3 · 9H2O: An Efficient Catalyst for the One-Pot Synthesis of 3,4-Dihydropyrimidin-2(1H)-ones Both under Reflux or Solvent-Free Conditions - Eskandar Kolvari; Maryam Mirzaeeyan (Journal of Chemistry)
Al(NO3)3 · 9H2O efficiently catalyzes the three-component Biginelli reaction between an aldehyde, a β-dicarbonyl compound, and urea or thiourea in refluxing ethanol and solvent-free (SF) conditions to afford the corresponding dihydropyrimidinones in high yields. The advantages of this method involve the easy procedure, the environmentally friendly process, and the low cost of the Lewis acid catalyst.